Stratigraphic-sedimentary evolution of a mixed siliciclastic-carbonate system in the Huizhou Sag of the Pearl River Mouth Basin, Northern South China Sea - Chen, Weitao; Liu, Jun; Peng, Guangrong; Wei, Zhe; Jia, Peimeng; Yao, Jiali; Wang, Zhina; Zhuo, Haiteng (Frontiers in Earth Science, 2024)
Mixed siliciclastic-carbonate systems are regulated interactively by factors such as siliciclastic sediment supply, carbonate production, sea-level change, tectonism, and climate conditions. These systems record vital information that aids in understanding ancient environments. This study used a merged 3D seismic volume, in conjunction with over 100 industrial wells, to systematically investigate the stratigraphic-sedimentary evolution of such a system within the Huizhou Sag of the Pearl River Mouth Basin, located on the northern continental shelf of the South China Sea. In total, six major sequence boundaries were identified for the Zhujiang Formation within the area, thus subdividing the interval into five typical third-order depositional sequences. Each of these sequences can be divided into a transgressive and a highstand systems tract. Lowstand or falling stage systems tracts were also recognized, the deposition of which was potentially in response to the uplifting process of the Dongsha Rise. During the deposition of the Zhujiang Formation, the Huizhou Sag may have undergone a sequential evolutionary history from delta-shore, to delta-shore-tidal-lagoon, to delta-shore-carbonate, and finally to delta-shore-shallow marine systems. This evolution responded to a varying degree of mixing processes, which was mainly regulated by siliciclastic sediment supply, confined paleomorphology, and local oceanic currents. Furthermore, the deposition of the Zhujiang Formation in the Huizhou Area was time-equivalent with the spreading process after the ridge jump of the South China Sea (23–16.5 Ma), providing valuable insights into sea-level fluctuations, provenance changes, and tectonic evolution. Our results may also shed light on the evaluation of lithologic traps and hydrocarbon sweet spots within mixed siliciclastic-carbonate systems.